2022
DOI: 10.1093/lambio/ovac042
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antioxidant, and antimicrobial activities of six commercial essential oils

Abstract: Essential oils (EOs) and their components extracted from medicinal and aromatic plants are used in several areas, such as perfumery and chemical, cosmetic, food, and pharmaceutical industries. Considering the different applications of EOs, this work aimed to screen the composition and the bioactivities properties of the EOs of Foeniculum vulgare, Helichrysum stoechas, Mentha pulegium, Pinus pinaster, Ruta graveolens, and Thymus mastichina. Gas chromatography–mass spectrometry revealed the presence of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For instance, spectrophotometric measurements are usually carried out after maintaining the prepared mixture of sample and free radicals (DPPH) for a particular duration. Although most often this duration was 30 min (e.g., [ 39 , 40 , 43 , 44 , 45 ]), in various published papers, it varied considerably: 10 min [ 46 ], 20 min [ 47 , 48 , 49 , 50 , 51 ], 25 min [ 52 ], 40 min [ 53 ], 50 min [ 42 ], 60 min [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], or 70 min [ 62 ]. Very often, the period after which the spectrophotometric measurements were performed was not mentioned (e.g., [ 63 , 64 , 65 ]).…”
Section: Methods Available For Antioxidant Testing Of Essential Oilsmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, spectrophotometric measurements are usually carried out after maintaining the prepared mixture of sample and free radicals (DPPH) for a particular duration. Although most often this duration was 30 min (e.g., [ 39 , 40 , 43 , 44 , 45 ]), in various published papers, it varied considerably: 10 min [ 46 ], 20 min [ 47 , 48 , 49 , 50 , 51 ], 25 min [ 52 ], 40 min [ 53 ], 50 min [ 42 ], 60 min [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], or 70 min [ 62 ]. Very often, the period after which the spectrophotometric measurements were performed was not mentioned (e.g., [ 63 , 64 , 65 ]).…”
Section: Methods Available For Antioxidant Testing Of Essential Oilsmentioning
confidence: 99%
“…A variety of positive controls were used: ascorbic acid [ 47 , 52 , 58 , 70 , 71 , 72 , 73 , 74 ], alpha-tocopherol [ 45 , 52 , 64 , 75 , 76 , 77 ], BHA [ 45 , 55 , 74 , 78 , 79 ], BHT [ 42 , 44 , 45 , 54 , 58 , 67 , 76 , 78 , 80 , 81 ], beta-caryophyllene [ 64 ], caryophyllene oxide [ 64 ], quercetin [ 42 ], tannic acid [ 82 ], gallic acid [ 60 , 83 ], thymol [ 84 ], and even Thymus vulgaris essential oil [ 62 ].…”
Section: Methods Available For Antioxidant Testing Of Essential Oilsmentioning
confidence: 99%
See 2 more Smart Citations
“…By combining these two, a synergistic effect can be harnessed [9]. Chamomile tea contains bioactive compounds, i.e., flavonoids and terpenoids, which have notable antimicrobial effects against numerous pathogens [10]. In addition, studies have demonstrated the inhibitory effects of chamomile extracts on bacterial growth, indicating their potential as a natural antimicrobial agent [11].…”
Section: Introductionmentioning
confidence: 99%